Cancer new treatment series: Comparison immune changes of HCC by scRNA-Seq following HELC treatment one case study - Yu, Baofa; Gao, Feng; Jing, Peng; Zhang, Peicheng; Zhang, Jian; Zheng, Guoqin (Trends in Immunotherapy, 2024)
Immunotherapy has emerged as a novel treatment strategy for many types of cancers, among them, liver cancer. The major advances and achievements in recent years is the use of programmed death-1 (PD-1) blockers for cancer treatment. Since patients’ immune systems are already weak following concurrent surgery plus chemo or radiotherapy, it is necessary to restore and awake their immune cells to maximize the effect for immune therapy. Methods: Liver cancers were treated twice with hapten enhanced local chemotherapy (HELC) like tumor lysates vaccine and following PD-1. Single-cell RNA sequencing (scRNA-seq) was used to analyze the changes of immune responses prior and after treatments. Results: We observed upregulation of cytotoxicity-related genes of CD8 effector T cells and NK cells in untreated tumor; Both Bmem and Naive B cells in untreated tumor showed a significant increase in MHC II signaling pathway-related genes, while MHC I-related genes was upregulated in plasma cells. Significant tumor size shrinkage was observed in both treated and untreated tumors following the HELC+PD-1 therapy. Conclusions: This study provides new biological insights into the abscopal effect at the single-cell level related to the composition of T and B cells in untreated liver cancers before and after major primary tumors treated by HELC. Our data showed that intra-tumor HELC can kill tumor cells and induced immune activity, which is likely vital in modifying tumor associate antigens (TAAs) into neo TAAs. It induces immune response just like vaccine can wake up immune cells and therefore increasing the efficacy of PD1 therapy.